Impact of natural or synthetic singletons in the capsid of human bocavirus 1 on particle infectivity and immunoreactivity - Fakhiri, Julia; Linse, Kai-Philipp; Schneider, Marc; Meister, Michael; Schnitzler, Paul; Grimm, Dirk (Journal of virology, 2020)
Human bocavirus 1 (HBoV1) is a parvovirus that gathers increasing attention due to its pleiotropic role as a pathogen and emerging vector for human gene therapy. Curiously, albeit a large variety of HBoV1 capsid variants has been isolated from human samples, only one has been studied as a gene transfer vector to date. Here, we analyzed a cohort of HBoV1-positive samples and managed to PCR amplify and sequence 29 distinct HBoV1 capsid variants. These differed from the originally reported HBoV1 reference strain in 32 nucleotides or four amino acids, including a frequent change of threonine to serine at position 590. Interestingly, this T590S mutation was associated with lower viral loads in infected patients. Analysis of the time course of infection in two patients for up to 15 weeks revealed a gradual accumulation of T590S, concurrent with drops in viral loads. Surprisingly, in a recombinant vector context, T590S was beneficial and significantly increased titers compared to that of T590 variants but had no major impact on their transduction ability or immunoreactivity. Additional targeted mutations in the HBoV1 capsid identified several residues that are critical for transduction, capsid assembly, or DNA packaging. Our new findings on the phylogeny, infectivity, and immunoreactivity of HBoV1 capsid variants improve our understanding of bocaviral biology and suggest strategies to enhance HBoV1 gene transfer vectors. - IMPORTANCE The family of Parvoviridae comprises a wide variety of members that exhibit a unique biology and that are concurrently highly interesting as a scaffold for the development of human gene therapy vectors. A most notable example is human bocavirus 1 (HBoV1), which we and others have recently harnessed to cross-package and deliver recombinant genomes derived from another parvovirus, the adeno-associated virus (AAV). Here, we expanded the repertoire of known HBoV1 variants by cloning 29 distinct HBoV1 capsid sequences from primary human samples and by analyzing their properties as AAV/HBoV1 gene transfer vectors. This led to our discovery of a mutational hot spot at HBoV1 capsid position 590 that accumulated in two patients during natural infection and that lowers viral loads but increases vector yields. Thereby, our study expands our current understanding of HBoV1 biology in infected human subjects and concomitantly provides avenues to improve AAV/HBoV1 gene transfer vectors.